Intellectual capital and firm performance: the moderating role of CSR in Sri Lanka’s materials sector - Thujinthan, R.; Tharshiga, P. (University of wayamba, Sri Lanka, 2025)
This study examines the moderating effect of Corporate Social Responsibility on the relationship between Intellectual Capital and firm performance, focusing on companies listed on the Colombo Stock Exchange in Sri Lanka from 2016 to 2022. Using a sample of 18 firms in the material sector, data were analysed through descriptive statistics, correlation analysis, variance inflation factor analysis, and panel data analysis in E-Views. The findings indicate that Human Capital Efficiency and CSR significantly impact Return on Assets(ROA). In contrast, structural capital efficiency and capital employed efficiency did not exhibit substantial effects on return on equity (ROE). The Hausman test results suggest that a random effects model is appropriate for ROA, while a fixed effects model is suitable for ROE. Based on these findings, businesses should prioritise investments in human capital through employee training, development, and innovation to enhance financial performance. Additionally, firms should align CSR initiatives with their strategic goals to maximise benefits. Policymakers can use these insights to establish industry-specific regulations encouraging sustainable business practices and resource efficiency. Furthermore, investors and stakeholders can leverage this knowledge to assess financial sustainability and CSR effectiveness, leading to informed investment decisions that align with long-term value creation. This study contributes to intellectual capital, CSR, and financial performance literature, offering practical implications for corporate leaders, policymakers, and investors.
Keywords: Intellectual capital; Corporate social responsibility; Firm performance; Human capital efficiency and structural capital